Autoimmune Hepatitis - Fatima Safira Alatas; Gryselda Hanafi; Lestari Kanti Wilujeng; Nielda Kezia Sumbung (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Autoimmune hepatitis (AIH) is a condition caused by self-perpetuating immune response towards hepatocytes in liver. In children, AIH may progressed more rapidly compared to adults. Thus, early diagnosis and prompt treatment are the key for successful management of AIH. Five main characteristics of AIH include female predominance, increased IgG or hypergammaglobulinemia, circulatory autoantibody seropositivity, and hepatitis interface from the histological finding. Liver biopsy is needed to evaluate the degree of damage and to confirm the diagnosis. The standard regiment for AIH include prednisone (or prednisolone) and azathioprine. Other alternative treatments available for non-responder, such as mycophenolate mofetil, tacrolimus, cyclosporine, budesonide, rituximab, and infliximab. AIH treatment is recommended to be taken minimally for 2-3 years before attempting treatment termination.